2008
DOI: 10.2217/14622416.9.10.1437
|View full text |Cite
|
Sign up to set email alerts
|

Variants of Dopamine and Serotonin Candidate Genes as Predictors of Response to Risperidone Treatment in First-Episode Schizophrenia

Abstract: These data suggest that the SNPs in DRD2 and AKT1 may influence the treatment response to risperidone in schizophrenia patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
2
12

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(114 citation statements)
references
References 47 publications
9
91
2
12
Order By: Relevance
“…This indicates a possible, partial role for the Taq1A polymorphism in response to aripiprazole (70). Two other previous studies in 2008 both also had positive findings in relation to Taq1A and clinical response to aripiprazole using the PANSS scale (71 [rs3803300] and AKT1-SNP5 [rs2494732]) were significantly associated with response to risperidone, using the PANSS scale (72).…”
Section: Pharmacodynamicsmentioning
confidence: 55%
“…This indicates a possible, partial role for the Taq1A polymorphism in response to aripiprazole (70). Two other previous studies in 2008 both also had positive findings in relation to Taq1A and clinical response to aripiprazole using the PANSS scale (71 [rs3803300] and AKT1-SNP5 [rs2494732]) were significantly associated with response to risperidone, using the PANSS scale (72).…”
Section: Pharmacodynamicsmentioning
confidence: 55%
“…Individuals with the Ser311Cys polymorphism, the fourth polymorphism of the gene, specifically the Ser/Ser genotype, were prone to respond to Risperidone treatment in a study with 123 Chinese participants [49] and demonstrated a decrease in cAMP synthesis inhibition in a study with 50 Japanese participants [50]. For the A-241G polymorphism, Asian individuals with A allele or A/A genotype showed a positive improvement to Risperidone treatment in a study with 125 Chinese participants [51] and in study with 120 Japanese participants [30]. However, American individuals with the A allele or A/A genotype showed a delayed response to Risperidone treatment in a study with 61 Caucasian and African American participants [44].…”
Section: Drd2mentioning
confidence: 96%
“…Two studies, one with a sample composed of 99 Chinese participants [28] and one with 123 Chinese participants [29] have shown a notable association among the T/T genotype and an improved response to Clozapine and Risperidone treatment in Han Chinese participants [28,29]. However, two other studies, one with 120 Japanese participants [30] and one with 173 Caucasian and African American participants [31], did not show any association between the treatment response and genetic variance of the 5HT6 gene (Table 1).…”
Section: Ht6mentioning
confidence: 99%
See 1 more Smart Citation
“…Полиморфный вариант Variable Number Tandem Repeats (48-bp VNTR), состоящий из повторных участков, расположен-ный в 3-м ýкзоне, активно изучался, однако дал противоречивые данные c подавляющим боль-шинством негативных результатов [62]. VNTR считается особенно важным, так как кодирует участок рецептора, вовлеченного в стыковку с G-белком, и чем длиннее ýтот участок за счет повторений, тем меньше становится аффинность рецептора к клозипину [63].…”
Section: гены кодирующие продукты которые участвуют в фармакодинамиunclassified